Child abuse interacts with hippocampal and corpus callosum volume on psychophysiological response to startling auditory stimuli in a sample of veterans - Young, Dmitri A. (J Psychiatr Res, 2019)
Child abuse (CA), which is linked to posttraumatic stress disorder (PTSD), has been associated with a reduction in both hippocampal and corpus callosum (CC) volume. However, few studies have explored these relationships on psychophysiological variables related to trauma exposure. Therefore, we assessed whether the interaction between CA and hippocampal and CC volume were associated with enhanced fear potentiated psychophysio-logical response patterns in a sample of Veterans. 147 Veteran participants who were part of a larger study of Gulf War Illness were exposed to startling sounds in no, ambiguous, and high threat conditions and also provided MRI data. The Clinician Administered PTSD Scale and Trauma History Questionnaire were used to measure PTSD and CA respectively. Psychophysiological response was measured by EMG, SCR, and heart rate. Repeated-measures mixed linear models were used to assess the significance of CA by neural structure interactions. CA interacted with both hippocampal and CC volume on psychophysiological response magnitudes, where participants with CA and smaller hippocampal volume had greater EMG (p < 0.01) and SCR (p < 0.05) magnitudes across trials and over threat conditions. Participants with CA and smaller CC volume had greater SCR magnitudes across trials and over threat conditions (p < 0.01). Hippocampal and genu volume mediated CA and psychophysiological response magnitude. CA may impact psychophysiological response via a reduction in hippocampal and CC volume. Volumetric reduction in these structures may indicate a neurofunctional, CA-related increase in threat sensitivity, which could portend increased PTSD susceptibility and adverse interpersonal and social consequences across the lifespan.